The division of labor and the market for organizations - Assar Lindbeck; Dennis J. Snower (The Research Institute of Industrial Economics (IUI), 2000)
The paper examines the determinants of the division of labor within firms. It provides an explanation of the pervasive observed changes in work organization away from the traditional functional departments and towards multi-tasking and job rotation. Whereas the existing literature on the division of labor within firms emphasizes the returns from specialization and the need for coordination of the work of different workers, the present analysis focuses on the returns from multi-tasking, which is shown to arise from informational and technological complementarities among tasks as well as from the exploitation of the versatility of human capital. The paper also explores how the move towards multi-tasking can affect the labor market, and the distribution of firms across organizational forms.
Keywords: 330; Arbeitsorganisation; Reorganisation; Arbeitsteilung; Verbundvorteil; Theorie der Unternehmung; Organisationstheorie; Industrieökonomik; Arbeitsmarkt; Theorie